Determination of the Complex Composition by the Method of Isomolar Series (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This paper describes experimental methods for the separation of nickel ions from the adsorbent using dimethylglyoxime in the regeneration of adsorbents.